Framework for Raising Cyber-Awareness to Prevent Cybercrimes Among Generation Z - Shereen KHAN; Nasreen KHAN; Swee Leng TAN; Anusuyah SUBBARAO; Booi Chen TAN (Communications of International Proceedings, 2022)
As the globe rapidly transitions to a digital economy, cybercrime is on the rise at an alarming rate. Cybercrime has increased, with young people being an especially vulnerable target. As a result, more study is needed to identify those who are most vulnerable and develop effective intervention measures. The study's objective is to look into the impact of social media knowledge sharing on cybercrime awareness and the function of offline social group influence in avoiding cybercrimes among Generation Z. The main output of the research is to produce a model that prevents cybercrimes among generation Z. This study suggests that education sectors develop a cyber security culture in which everyone learns about and respects the privacy and information security. Furthermore, parents play an important role in sharing and recognizing their children's grasp of cyber security and hazards. Most essential, government and commercial entities should use social media platforms to raise awareness.
Keywords: knowledge; awareness; social group; prevention; cybercrimes